Advanced Silicon Chemistry in Australia: Forming Strong Links with Asia - Clarke, Stephen; Kim-Anh Thi Nguyen; Markovic, Elda; Trout, Neil; Ginic-Markovic, Milena; Matisons, Janis; Owen, Michael; Graiver, Daniel; Wargadipura, Agus Hadi Santosa; Habibie, Sudirman; Gustiono, Dwi; Yoo, Bok Ryul; et al. (WILEY-V C H VERLAG GMBH, 2017)
This paper details Australian commercial and academic silicon research. Areas of interest include silicon metal, polysiloxane polymers, copolymers, cyclics, emulsions, microemulsions, silanes, silane coupling agents, sol-gel chemistry and water-treatments, porous silicon, polysiloxane degradation, silicon hydrogel contact lenses, silanolate synthesis, siloxane interfacial polymerisation, hydrosilylation, polysiloxane electrolytes for lithium ion batteries, silanes for PBX materials, octafunctionalized polyhedral oligomeric silsesquioxanes (POSS), POSS hybrids, sol-gel hydrogenation catalysts, silane modification of silica, sol-gel energy storage, silicate grout stabilisation, GeoPolymer concretes, aerogel insulating foams, Phaco-Ersatz Accommodating GelIntraocular Lens technologies. Strong collaborative opportunities, in silicon, with Asia, exist with organisations such as: 1)The Asian Silicon Society and 2)The Agency for the Assessment and Application of Technology (BPPT) Indonesia.
Keywords: POLYHEDRAL OLIGOMERIC SILSESQUIOXANE; LENS PHACO-ERSATZ; INITIATED POLYMERIZATION; REFRACTIVE-INDEX; ACCOMMODATION; COPOLYMERS